Reducing firearm injury and death : a public health sourcebook on guns - Karlson, Trudy Ann (Rutgers University Press, 1997)
Two experts in public health and injury control show readers how guns are products, designed to injure and kill, and how changes in the design, technology, and marketing of firearms can lead to reductions in the number of injuries and fatalities.